FORMATION OF STRATEGIC REGIONAL DEVELOPMENT OF GAZUZI TOURISM AND RECREATION AFTER THE WAR IN UKRAINE - HORIACHOVA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the current conditions of the war (Russia against Ukraine), and before that the coronovirus pandemic, the tourism industry, one of the first to suffer and receive significant financial losses, also lost human resources and infrastructure. Therefore, at present, the question of the developed strategies for the development of tourism both in the country and at the regional level, and especially the question of the resort and recreation sphere, is acute. The potential of the sphere of tourism and recreation of the opportunities and resources of the natural, infrastructure of the Transcarpathian region, which after the war can be directed to the development of the tourist and recreational business and bring significant economic profit, has been studied. It was found that the functioning of the tourism and recreation industry is determined by three imperatives: economic, social, and ecological. The necessity of sanatorium-resort institutions in Transcarpathia is substantiated, the issue will become especially acute after the war, when it will be necessary to heal children and improve their psychological state of health, disturbed by the war. The necessity of developing a regional level mechanism for the development of tourism and recreation in Ukraine after the end of the war, aimed at monitoring changes in the external and internal environment of the functioning of regional tourism and recreation or introducing changes for better development of the industry and opportunities, which will contribute to competitiveness in achieving strategic goals, is proposed. and economic development. At the same time, cooperation between authorities and local self-government is necessary, and most importantly, support for the tourism sector.
Keywords: development of tourism and recreation; natural resources and geographic features; health resorts; tourism development strategy; socio-economic opportunities